Spatial proximity effects on cognitive processing of multimedia learning among college students: evidence from functional near-infrared spectroscopy - Ma, Yan; Peng, Qiuyue; Long, Bowen (Frontiers in Psychology, 2025)
AimFrom a cognitive perspective, the spatial proximity effect suggests that during the process of the brain processing information, the degree of information processing and construction varies with spatial distance. However, most previous studies mainly relied on behavioral experiments.MethodsTo investigate the neural mechanisms underlying the spatial proximity effect, this study employed functional near-infrared spectroscopic imaging (fNIRS) to monitor and analyze the neural activity in the prefrontal cortex of 36 college students while they engaged in learning tasks with different graphic formats (proximity vs. separation). In addition, the study also explored how disciplinary differences affect the strength of spatial proximity effects and corresponding brain activation patterns.ResultsThe findings revealed that activation levels in the middle temporal gyrus, frontal pole, and dorsolateral prefrontal cortex were significantly higher in the spatial proximity condition compared to the spatial separation condition, accompanied by an improved rate of correct answers. These results suggest that the spatial proximity of illustrations and text can significantly enhance learning outcomes. Furthermore, when the subjects were learning physics, the activation level of the superior temporal gyrus was significantly higher than that when they were learning English and geography. Moreover, under the adjacent condition, the accuracy rate of learning performance was higher, which reveals that the spatial proximity effect is significant under the conditions of learning English, Geography, and Physics and that the superior temporal gyrus may be related to the neural mechanism of the spatial proximity effect in different disciplines.ConclusionThis study provides evidence for the neural mechanisms behind the spatial proximity effect and verifies the influence of different disciplines on this effect. Provided a practical basis for media teaching design from the perspective of cognitive processing.